2004
DOI: 10.1590/s0370-44672004000400014
|View full text |Cite
|
Sign up to set email alerts
|

Effects of deformation on the microstructure of a Ti-V microalloyed steel in the phase transition region

Abstract: Microalloyed steels are used in the forging of many automotive parts like crankshafts and connecting rods. They are hot worked in a sequence of stages that includes the heating to the soaking temperature, followed by forging steps, and finally the controlled cooling to define the microstructure and mechanical properties. In this work it was investigated the thermomechanical behavior and the microstructural evolution of a Ti-V microalloyed steel in the phase transition region. Torsion tests were done with multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Cross wedge rolling (CWR), an innovative metal forming process whereby a cylindrical billet is plastically deformed into a stepped shaft under the action of two dies with wedges moving tangentially to each other, is mostly used in manufacturing steel products such as camshafts and connecting rods in the automotive industry [1]. It has been promoted to other industries such as high-speed railways [2] and nuclear reactors [3] where materials such as titanium alloys [2,4], aluminium alloys [5] and 42CrMo/Q235 laminated materials [6,7] are used. It was reported that the annual production of CWR parts in China reached over 2 billion pieces with a gross weight of over 400,000 tons in 2018 [8].…”
Section: Introductionmentioning
confidence: 99%
“…Cross wedge rolling (CWR), an innovative metal forming process whereby a cylindrical billet is plastically deformed into a stepped shaft under the action of two dies with wedges moving tangentially to each other, is mostly used in manufacturing steel products such as camshafts and connecting rods in the automotive industry [1]. It has been promoted to other industries such as high-speed railways [2] and nuclear reactors [3] where materials such as titanium alloys [2,4], aluminium alloys [5] and 42CrMo/Q235 laminated materials [6,7] are used. It was reported that the annual production of CWR parts in China reached over 2 billion pieces with a gross weight of over 400,000 tons in 2018 [8].…”
Section: Introductionmentioning
confidence: 99%